ANALISIS FAKTOR RESIKO PENYEBAB PELAYANAN ANTIBIOTIK TANPA RESEP DOKTER DI APOTEK: A REVIEW - Tupak, Helma Malini Marol; Vikasari, Suci Nar (Jurnal Buana Farma, 2025)
The dispensing of antibiotics without a doctor’s prescription in pharmacies remains a common practice and contributes significantly to the rise of antibiotic resistance, which poses a major threat to public health. This phenomenon is driven by interrelated risk factors, including easy access, limited public knowledge, socioeconomic influences, and weak regulatory enforcement. This study aims to identify the risk factors underlying the dispensing of antibiotics without prescriptions in pharmacies. A literature review was conducted by collecting and analyzing Indonesian and English journal articles published between 2015 and 2025. Data were retrieved from Google Scholar and PubMed using keywords related to the sale and purchase of antibiotics without a doctor’s prescription. The findings were analyzed narratively and grouped into three perspectives: business actors, patients or consumers, and regulators. From the perspective of business actors, the risk factors include pharmacy staff attitudes that facilitate non-prescription antibiotic sales, financial motivations, consumer pressure and demand, and insufficient professional knowledge. From the perspective of patients, risk factors involve the ease of obtaining antibiotics without a prescription, economic, social, and cultural influences, lack of awareness and understanding, and prior personal experiences of antibiotic use. From the perspective of regulators, weak supervision and poor law enforcement remain key drivers of this practice. In conclusion, comprehensive efforts are required to address this issue. These include strengthening regulations, improving public education, and enhancing the training of pharmacy personnel. Such interventions are critical to preventing antibiotic misuse and mitigating the long-term consequences of antibiotic resistance on public health.